Achieving success with the engineering dissertation - Gratton, Petra (Springer, 2020)
Achieving Success with the Engineering Dissertation describes the different types of dissertation, how to pick the best project and how a student can prepare themselves to succeed with their own dissertation. The authors explain how best to plan and execute the project, including the roles of the student, supervisor and project sponsor, and what they should expect from each other. Further material includes details of competitions that can be entered with dissertation projects, presentation of data, using the dissertation in job interviews, and creating research publications. Achieving Success with the Engineering Dissertation will be of use to both undergraduate and postgraduate students in all fields of Engineering, and to their supervisors.